Analisis Tingkat Kemampuan Berpikir Kritis Gelombang Mekanik Melalui Pembelajaran Dengan Pendekatan Konflik Kognitif - Zul Hidayatullah; Muh. Makhrus; I Wayan Gunada (Department of Physics Education, Universitas Mataram, 2018)
This study aim to analyze the critical thinking level of mechanical wave in the students of MAN 2 Mataram through Cognitive Conflict Approach. This research is a pre-experimental study with design only pretest-posttest group design. The population in this study is all students of class XI MIA MAN 2 Mataram, amounting to 257 students. Research sampling using purposive sampling technique, so selected XI class MIA 1, XI MIA 2, and XI MIA 4 as an experimental class that will be given treatment in the form of cognitive conflict approach. Data collection of critical thinking ability is done by description test as much as 5 problem and at the learning process obtained through LKPD. The results of hypothesis test analysis using parametric test paired sample t test and show that Ho rejected and Ha accepted, while the level of critical thinking ability included in category is very high for class XI MIA 1 and high category for class XI MIA 2 and XI MIA 4. The conflict cognitive approach applied successfully to increase the critical thinking ability.